Peningkatan Prestasi Belajar Melalui Strategi Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Mata Pelajaran IPS Siswa Kelas III SDN Kalianget Barat II Kab. Sumenep - Tri Sutrisno (IAIN Madura, 2020)
This research aims to; Want to know an increase in social studies learning achievement after the implementation of cooperative learning model Teams Assisted Individualization class III students of SDN Kalianget Barat II Kab. Sumenep